2016
DOI: 10.1016/j.amjmed.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Body Mass Index: Advantages of Abdominal Measurements for Recognizing Cardiometabolic Disorders

Abstract: BACKGROUND The clinical recognition of cardiometabolic disorders might be enhanced by anthropometry based on the sagittal abdominal diameter (SAD; also called “abdominal height”) or waist circumference rather than on weight. Direct comparisons of body mass index (BMI, weight/height2) with SAD/height ratio (SADHtR) or waist circumference/height ratio (WHtR) have not previously been tested in nationally representative populations. METHODS Nonpregnant adults without diagnosed diabetes (ages 20–64 years; n = 307… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
2
24
0
1
Order By: Relevance
“…While neither of these studies used the gold standard to measure glucose metabolism, OGTT, they corroborated the present results using HbA1c values [42, 46]. …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…While neither of these studies used the gold standard to measure glucose metabolism, OGTT, they corroborated the present results using HbA1c values [42, 46]. …”
Section: Discussionsupporting
confidence: 86%
“…Only two previous studies have been conducted on a large national sample of US adults to investigate the relationship between SAD and glucose metabolic disturbances [42, 46]. While neither of these studies used the gold standard to measure glucose metabolism, OGTT, they corroborated the present results using HbA1c values [42, 46].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Earlier cross-sectional studies have demonstrated that WHtR [12,13,21] or SADHtR [21] were similarly associated with traditional risk factors for cardiometabolic disease, and that these associations were generally stronger than those with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Since the supine sagittal abdominal diameter (SAD, also called “abdominal height”) correlates strongly with the amount of visceral fat [15,16] and with traditional cardiometabolic risk markers [1719], several authors have extended consideration to the SAD/height ratio (SADHtR) as yet one more alternative to the BMI [10,11,20,21]. Beginning in 2011, the supine SAD has been measured routinely in the U.S. National Health and Nutrition Examination Survey (NHANES) along with waist circumference, height, and weight.…”
Section: Introductionmentioning
confidence: 99%